Pengaruh Faktor Sosial Demografi terhadap Kemiskinan Anak di Indonesia Tahun 2021 : - Elza Robasa; I Made Arcana (Politeknik Statistika STIS, 2022)
Child poverty is a state when children experience a lot of loss of their basic rights, such as adequate food, housing, health, safe drinking water. Proper sanitation facilities, information, education, and access to services. Fulfillment of children’s basic rights during their growth and development needs to be considered in order to become a quality future generations of the nation. The quality of children whose basic rights are not fulfilled has potential to create poor individuals and trapped in a cycle of poverty. The purpose of this study is to find out the general description of child poverty in multidimensional manner using Multiple Overlapping Deprivation Analysis (MODA) and identify socio-demographic factors that affect child poverty in Indonesia in 2021 by applying a binary logistic regression model. The results showed that the percentage of multidimensional child poverty in Indonesia in 2021 was 49.5 percent. In addition, child’s age, child’s gender, age of household head, gender of household head, working status of household head, education of household head, parenting status, number of household members significantly affect the multidimensional poverty of children in Indonesia. The tendency of children in the age group 0-4 years to experience deprivation on children's rights in a multidimensional manner was 3.5 times compared to children in the age group 5-17 years.